The International Society for Biological and Environmental Repositories. Abstracts from Its Annual Meeting. (My University, 2023)
The abstracts that follow demonstrate the broad range of timely issues addressed in the contributed Oral and Poster presentations at ISBER's 2023 Annual Meeting & Exhibits.
Keywords: cryopreservation; cryobanking